The Role of Digital Marketing Strategies in Strengthening Information Literacy at Gramedia - Aidil Adha Januando; Naufalia Rahmadhani; Dewi Istiqomah (Codex: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
A This study was motivated by Indonesia’s relatively low level of digital literacy, which has not yet kept pace with the rapid advancement of digital technologies and media usage. Gramedia, as a commercial literacy institution, has sought to utilize digital marketing strategies to strengthen reading culture and public information literacy. The purpose of this study is to analyze how Gramedia’s digital marketing strategies contribute to enhancing users’ informational awareness, evaluative ability, and literacy participation. A descriptive qualitative approach was applied, employing semi-structured interviews with three key informants—namely a digital content manager, a marketing staff member, and an active user of Gramedia Digital alongside document analysis from multiple Gramedia digital platforms. Data were analyzed using thematic analysis to identify emerging patterns and meanings within the digital marketing practices. The results indicate that Gramedia’s digital marketing has evolved into an effective educational medium, transforming users’ behaviour from passive information consumers into active participants within the literacy ecosystem. The study concludes that digital marketing strategies designed with educational values can serve as strategic instruments for strengthening information literacy while providing both conceptual and practical contributions to the advancement of Library and Information Science in the digital transformation era.